Influence of environmental variability on phylogenetic diversity and trait diversity within Calligonum communities - Wang, Jian-Cheng; Yang, Hong-Lan; Wang, Xi-Yong; Shi, Wei; Pan, Bo-Rong (EXCLI journal, 2014)
Since phylogenetic data provide the evolutionary history of the species and traits are the result of adaptation to the environmental conditions, joint analysis of these two aspects and ecological data may illuminate that how ecological processes affect the evolution of species and assembly of communities. In this study, we compared the community structure of sibling communities in order to illuminate the influence of environmental variability. We chose different Calligonum communities as research subjects which grow in active sand dunes and stabilized sand fields. Our results show that species which co-occurred in C. rubicundum community have greater phylogenetic evenness compared to species in other communities where co-occurring plants had similar traits. Soil variability might legitimately explain this result. Based on the similarity between the pattern of trait diversity and the pattern of phylogenetic diversity, we inferred that the evolution of traits is conservative and species of all but C. rubicundum communities are under more intense selection pressure.